Comparative Evaluation of the Phytochemical and Morphological Analysis and Anti-Inflammatory Effect of Lantana camara on Mice Animal Model - alzwaini, rusol; Mohammed Saeed, Orooba (The Iraqi Journal of Veterinary Medicine, 2024)
The aim of the study is to evaluate the phytochemical and morphological characterization between Iraqi and America Lanata camara extracts and to evaluate their inhibition effect on the egg albumin-induced paw inflammation. Successive maceration was used to eliminate the leaves of L. camara. The bioactive substance components present in the extract were identified using gas chromatography-mass spectrometry (GC-MS) analysis. In addition, HPLC analysis was performed for the detection of active compounds. The paw edema induced by injecting egg albumin (0.1ml) in both right and left hind-paw and the percentage inhibition as well as cell count, and skin thickness was measured. The initial phytochemical screening yielded positive test results for phenolic compounds, glycosides, tannins, saponins, anthraquinones, polysaccharides, and terpenoids. The results of GC-MS analysis of Iraqi and American leaves showed oleic acid (22.65%, 36.69%), octadecanoic acid (26.58%, 13.49%) and hexadecanoic acid (7.06%,14.52%), respectively, were the main compound in both extracts. The HPLC analysis indicated the presence of vitamin K in Iraqi and American leaves (9.52%, 9.77%) respectively, while there are no other research publications indicated to such results. The concentration 0.05% of Iraqi and America L. camara showed a significant inhibition effect (99.7%) of inflammation. The cell counts and skin thickness showed a significant decreased when treated with both extracts of L. camara. In conclusion, this study showed that the phytochemical composition of lantana camara leaf extract varies depending on the geographical region. The findings also suggest that this extract, contains various bioactive compounds that could be a valuable resource for developing pharmaceuticals to treat different diseases. The study also found that the extract has a significant anti-inflammatory effect and could be a promising option for inhibition of inflammation.